«In the interests of increasing the influence and prestige of the USSR in the Middle East». Report of the soviet representative in Turkey to authorities of the People's Commissariat for Foreign Affairs of the USSR on situation in the Patriarchate of Constantinople in 1924 - Aleksandr Mazyrin (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This publication introduces an important document from the Archive of foreign policy of the Russian Federation. This document illustrates the attitude of the People's Commissariat for Foreign Aff airs of the USSR towards the Patriarchate of Constantinople at one of the most critical moments of its history (April 1924) and allows one to assess the Commissariat’s good awareness of the state of aff airs in the Eastern church. The published source shows difficult situation of the primary Patriarchate on the one hand, and its strong involvement in political intrigues on the other hand, which the author of the document (presumably, the representative of the USSR in Turkey Ya. Z. Surits) cynically offered to make use of. The published analytical report pays much attention to the problem of the so-called Anatolian church (better known as the “Turkish Orthodox Church”). It is noteworthy that the Soviet diplomat did not give unambiguous assessments and recommendations to his Moscow administration. His key suggestion was to send a representative of the Russian Renovationist schism to Istanbul and then use him in order to infl uence the Patriarchate of Constantinople in Soviet interests. This proposal appeared to be interesting to the administration of the Commissariat, but for some reason was not implemented, which partially prevented the worst-case scenario of the development of relations between the Russian and Constantinople Churches; in this worst scenario, the Fanar would have become fully affiliated with the Soviet Renovationism (in the end, this affi liation was less defi nitely pronounced).